MINISTÉRIO PÚBLICO BRASILEIRO: ENTRE O EXERCÍCIO DO CONTROLE SOCIAL E SUA ATUAÇÃO EXTRAPENAL PREVENTIVA - Caruncho, Alexey Choi (2011)
Analysis of the criminal phenomenon fighting by Brazilian Public Ministry, body endowed with constitutional legitimacy that is still seeking a suitable role model with the profile designed by the Republic Constitution of 1988. Diagnosis of the problems and proposals for reconciling the interpretation of penal activity and the extrapenal activity of the institution. To this end, it starts a ministerial historical approach, analyzing it from the profile assumed along of the several periods, whether being under foreign jurisdiction field or the native one. Particularly in this latter regard, the colonial, imperial and republican phases are appreciated, linking them to the profile assumed by the institution at any time. It is held, moreover, a criminological digression, seeking to understand the several ways of the criminal phenomenon interpretation, as directly linked with the activity of the Public Ministry in its work. The study of crime, in this sense, is effected by means of its etiological conception, its critical interpretation and the own post-critical current. Since then, it starts facing the issue initially presented. At first, through the discussion devoted to the actions of the Public Ministry as an advocate of the democratic regime and penal persecutor by the Brazilian Public Ministry, raising questions of the possibility of a crisis existence. In the second and last moment, considering the extrapenal acting of the Brazilian Public Ministry in favor of a possible "social transformation", especially through criminal prevention. I don’t intend to provide final answers, the study will seek to contribute to the discussion involving both the role played by the Brazilian Public Ministry as one of the agents responsible for formal social control, as the lack of basic assumptions to even begin the understanding of what it would be and what the limits of this ministerial function would be as supposed transforming agent. Analysis of the criminal phenomenon fighting by Brazilian Public Ministry, body endowed with constitutional legitimacy that is still seeking a suitable role model with the profile designed by the Republic Constitution of 1988. Diagnosis of the problems and proposals for reconciling the interpretation of penal activity and the extrapenal activity of the institution. To this end, it starts a ministerial historical approach, analyzing it from the profile assumed along of the several periods, whether being under foreign jurisdiction field or the native one. Particularly in this latter regard, the colonial, imperial and republican phases are appreciated, linking them to the profile assumed by the institution at any time. It is held, moreover, a criminological digression, seeking to understand the several ways of the criminal phenomenon interpretation, as directly linked with the activity of the Public Ministry in its work. The study of crime, in this sense, is effected by means of its etiological conception, its critical interpretation and the own post-critical current. Since then, it starts facing the issue initially presented. At first, through the discussion devoted to the actions of the Public Ministry as an advocate of the democratic regime and penal persecutor by the Brazilian Public Ministry, raising questions of the possibility of a crisis existence. In the second and last moment, considering the extrapenal acting of the Brazilian Public Ministry in favor of a possible "social transformation", especially through criminal prevention. I don’t intend to provide final answers, the study will seek to contribute to the discussion involving both the role played by the Brazilian Public Ministry as one of the agents responsible for formal social control, as the lack of basic assumptions to even begin the understanding of what it would be and what the limits of this ministerial function would be as supposed transforming agent.